Base Pressure Control with Semi-Circular Ribs at Critical Mach Number - Khan, Ambareen; Khan, Sher Afghan; Akhtar, Mohammed Nishat; Aabid, Abdul; Baig, Muneer (Fluid dynamics & materials processing, 2024)
When better fuel-air mixing in the combustion chamber or a reduction in base drag are required in vehicles, rockets, and aeroplanes, the base pressure control is activated. Controlling the base pressure and drag is necessary in both scenarios. In this work, semi-circular ribs with varying diameters (2, 4, and 6 mm) positioned at six distinct positions (0.5D, 1D, 1.5D, 2D, 3D, and 4D) inside a square duct with a side of 15 mm are proposed as an efficient way to apply the passive control technique. In-depth research is done on optimising rib size for various rib sites. According to this study, the base pressure rises as rib height increases. Furthermore, the optimal location for the semi-circular ribs with a diameter of 2 mm is at 0.5D. The 1D location appears to be optimal for the 4 mm size as well. For the 6 mm size, however, the 4D position fills this function.